Electrothermal instabilities observed by x-ray radiography of underwater sub-microsecond electrical explosions of aluminum, silver, and molybdenum wires - Grikshtas,R; Asmedianov,N; Belozerov,O; Efimov,S; Strucka,J; Yao,Y; Lukic,B; Rack,A; Bland,SN; Krasik,YE (Physics of Plasmas, 2025)
We present measurements of the wavelength of electrothermal instabilities (ETI) formed during underwater electrical explosions of aluminum (Al), silver (Ag), and molybdenum (Mo) wires. Wires were exploded using a ∼450 ns rise time and ∼120 kA amplitude current pulse delivered by a pulse generator. Images of the exploding wires were captured by multi-frame synchrotron radiography at the ID19 beamline of the European Synchrotron Radiation Facility. Resolvable ETI was observed only in Al and Ag wires after the vaporization phase, whereas no such instabilities were detectable in Mo wires. Fourier analysis revealed that the ETI wavelengths in Al and Ag wires were comparable within the spatial resolution error, despite their different minimal instability wavelengths, which were predicted to develop during the melting phase. These minimal wavelengths were calculated using the linear ETI development theory and the simulated average wire temperature. The latter was calculated using one-dimensional hydrodynamic simulations, considering uniform current density across the wire cross-sectional area.